Smoking prevalence and affecting factors in students of ondokuz mayis university physicial education and sports academy - Pekşen, Yıldız; Canbaz, Sevgi; Sünter, A. Tevfik; Tunçel, Ebru K. (Journal of Dependence, 2005)
Objective: Tobacco is the second major cause of death in the world. The purpose of this study was to investigate in students of Ondokuz Mayıs University Physical Education and Sports Academy (PESA) in order to find out smoking prevalence and affecting factors.Method: A cross-sectional study was conducted between April 18 and 22, 2005 in the students, at PESA. Out of a total of 253 enrolled students, 207 (81.8%) agreed to participate in the study. A questionnaire was applied to participants under observation. Data were given as mean ± standard deviation (SD) and percentages. Analysis of data performed by using chi-square and student t tests.Results: Smoking prevalence was 14.0% in this study. While there was no statistically significant difference between participants, smoking and non-smoking, according to sex (p>0.05); there was statistically significant difference between participants, smoking and nonsmoking, according to any members smoking in family, accommodation and the place where the childhood was passed. The mean age of starting smoking, in girls and boys, were 16.1 ± 0.7 and 16.7 ± 3.2 years, respectively, and the difference was not statistically significant (p>0.05). Of the smokers, only 1 (3.4%) was reported that she/he smoking in places where smoking is prohibited such as hospitals, libraries and theatres. Of the smokers, 5 (17.2%) has tried to quit smoking once and 13 (44.8%) has tried to quit smoking more than once. Two participants were attended to an organized smoking cessation program.Conclusion: In conclusion, to decrease the prevalence of smoking, role models such as teachers, doctors, and parents, who presents a role model for youth, need to be educated about harmful affect of smoking, and quit campaigns should be organized.
Keywords: Smoking; student; sports; prevalence